Hugh Weiss. - Durozoi, Gérard; Weiss, Hugh (Paris : Somogy éditions d'art, 2000)
Born in the United States in 1925, Hugh Weiss has lived and worked in Paris since 1948. Naturalized French citizen, the few perceptible traces of America that he retains are the spelling of the first name, a caustic sense of humour and an Anglo-Saxon propensity for the pun. Considered by some as related to the Figuration Narrative movement in France, his work, however, is more dream-like, resolutely individualistic and completely unclassifiable. Hugh Weiss refuses current artistic trends and persistantly invents his own tragi-comic imagery which speaks of the strangeness of the world, of unforeseen meetings during unending voyages, of shuttling through life in an armchair, a biplane, a car, a boat, as a mustached elephant, an ardent swimmer... The colors of his paintings seem bright, but sudden unespected stridencies, discords, reveal an underlying irony. His artistic adventure, from the early fourties to the present day, is presented to 200 reproductions.
bibliog. p. 235-237
biog. p. 228-229
ind. tent. p. 230, gr. tent., coll. p. 231-233
Engels
Frans
boek
Keywords: Weiss, Hugh